The Challenges and Prospects of E-learning in National Open University of Nigeria - Olukayode Solomon Aboderin (Journal of Education and Learning (EduLearn), 2015)
The study investigated the challenges and prospects of e-learning in National Open University of Nigeria. It sought to find out Attitudes of students towards e-learning. The study investigated the various challenges of e-learning in NOUN. Also the studies investigated prospects of e-learning, availability of e-learning facilities and also determine the ICT competence of NOUN students. The design of the study is a descriptive survey type. The sample for the study consisted of 250 students randomly selected from all the faculties in National Open University of Nigeria, Akure Study Center. 50 students were drawn from each faculty using simple random sampling technique giving a total of 250 students (respondents). A questionnaire titled “Challenges and Prospects of E-learning in National Open University of Nigeria” designed by the research was used to collect data. The instrument was validated by expert in Computer Science, Educational Technology and Test and Measurement. To ensure the reliability of the instrument, a Cronbach alpha statistics technique was employed and a reliability coefficient of 0.84 was obtained. This value is high enough for a study of this nature. The data collected were analyzed through the use of descriptive statistics such as frequency count, percentage and bar chart. The result of the findings showed that: NOUN students show positive attitude towards the use of e-learning. Majority of the respondents agreed that NOUN does not have enough e-learning equipment and facilities. There are challenges affecting the utilization of e-learning in NOUN for instructional purposes. The study also revealed that e-exam adopted by NOUN contributes to students’ ICT competence and prospects of e-learning if fully implemented.